Pengaruh Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Puskesmas Cikalong Kab. Tasikmalaya - Divia Oktora; Arga Sutrisna; Arif Arif (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Performance is the output or final result of work done by employees in a certain period, the work done by employees must be in accordance with the provisions set by the organization for their employees. This study aims to determine the effect simultaneously or partially of the Communication variable and the Work Environment variable on the measured performance. The population used in this study was 50 employees of the Cikalong Health Center. The method used in this research is descriptive research with a quantitative approach. Sample selection using saturated samples. The sample used is the entire population, namely 50 employees of the Cikalong Health Center. Sources of data in this study are secondary data and primary data. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the results of the study it is concluded that communication and the work environment simultaneously have a significant effect on performance. Communication partially has a significant effect on performance. The work environment partially has a significant effect on performance.